2014
DOI: 10.1111/codi.12508
|View full text |Cite
|
Sign up to set email alerts
|

Same‐day assessment and management of urgent (2‐week wait) colorectal referrals: an analysis of the outcome of 1606 patients attending an endoscopy unit‐based colorectal clinic

Abstract: Flexible sigmoidoscopy, in the context of an endoscopy unit TWW clinic, allows same-day diagnosis of most patients referred with left-sided symptoms, and immediate reassurance and treatment of most benign diagnoses. For these patients, the use of routine WCI following a cancer-free FS does not appear to be beneficial. Adopting this system would significantly reduce the number of barium enemas and colonoscopies currently performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…The cancer detection rate in our study was only 3%, which is much lower than other reported series, with rates of 6-14% in a 2WW population. [20][21][22][23][24][25][26] Our detection rate may have been influenced by the exclusion of male patients. However, there is a suggestion that detection rates are falling 27 with referrals increasing, particularly following the Be Clear on Cancer campaign in 2012.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The cancer detection rate in our study was only 3%, which is much lower than other reported series, with rates of 6-14% in a 2WW population. [20][21][22][23][24][25][26] Our detection rate may have been influenced by the exclusion of male patients. However, there is a suggestion that detection rates are falling 27 with referrals increasing, particularly following the Be Clear on Cancer campaign in 2012.…”
Section: Discussionmentioning
confidence: 95%
“…Large numbers of patients are seen through this pathway but the literature shows that only 6-14% of patients referred via this route are diagnosed with cancer and this is decreasing over time. [20][21][22][23][24][25] Experience suggests that the secondary care system does not have the capacity for full investigation and management of the remaining patients with functional and benign colorectal disorders that may be identified. This could represent a potentially significant need for development of pelvic floor services.…”
mentioning
confidence: 99%
“…28 It has been suggested that there is scope within the NHS to reduce the diagnostic burden for patients and endoscopy services by implementing clinical protocols which incorporate the selective use of FS, in place of WCI, for the initial investigation of patients with symptoms suggestive of distal CRC. [29][30][31][32][33] For WCI to be avoided in favour of FS, diagnostic protocols using FS for first-line investigation must be able to demonstrate INTRODUCTION NIHR Journals Library www.journalslibrary.nihr.ac.uk favourable risk-benefit profiles, in which the benefits of this less invasive procedure are balanced against the risk of a missed diagnosis of proximal cancer. [34][35][36] The use of such protocols is likely to be most relevant in clinical practice for which the clinical index of suspicion for proximal colon cancer is low, for example when patient and symptom profiles favour a diagnosis of distal CRC.…”
Section: Computerised Tomography Colonographymentioning
confidence: 99%
“…For the most part, these have been retrospective analyses of patients presenting INTRODUCTION NIHR Journals Library www.journalslibrary.nihr.ac.uk through urgent 2-week wait referral pathways in England for the evaluation of symptoms suggestive of CRC. 29,32,[34][35][36] In an analysis of presenting symptoms in 2-week wait patients with proximal cancer, only 3.4% (7/206) of patients with a CIBH and/or rectal bleeding would have had their proximal cancer missed if FS had been the only investigation. 29 A lower miss rate was calculated in a separate study of patients with distal symptoms referred to a rapid access colorectal clinic.…”
Section: Tailoring Initial Investigations For Suspected Colorectal Camentioning
confidence: 99%
See 1 more Smart Citation